Repeatability and reproducibility of a new spectral-domain optical coherence tomography biometer and agreement with swept-source optical coherence tomography based biometer - Xin Li; Chak Seng Lei; Rui Ning; Luze Liu; Aodong Chen; Xinning Yang; Giacomo Savini; Domenico Schiano-Lomoriello; Xingtao Zhou; Jinhai Huang (Eye and Vision)
Abstract Background To assess the repeatability and reproducibility of the Colombo IOL biometer (Moptim, China), which utilizes spectral-domain optical coherence tomography (SD-OCT), in measuring ocular parameters of normal subjects and to compare its agreement with the swept-source optical coherence tomography (SS-OCT)-based IOLMaster 700 biometer (Carl Zeiss Meditec AG, Germany). Methods This prospective study included 91 eyes from 91 normal subjects. The evaluated parameters were axial length (AL), central corneal thickness (CCT), aqueous depth (AQD), anterior chamber depth (ACD), lens thickness (LT), flattest and steepest meridian keratometry (Kf and Ks), mean keratometry (Km), astigmatism (AST) magnitude, white-to-white (WTW) distance, and pupil diameter (PD). The within-subject standard deviation (Sw), test–retest repeatability (TRT), coefficient of variation (CoV), and intraclass correlation coefficient (ICC) were calculated to determine the repeatability and reproducibility. Paired t-tests and Bland–Altman plots with 95% limits of agreement (LoA) were employed to assess the agreement. Results With respect to intraobserver repeatability, the Sw and TRT values of all evaluated parameters were low. Except J45 and PD, the ICCs were all higher than 0.928. The reproducibility Sw and TRT values of Colombo IOL were also low, and ICCs were not lower than 0.900. Comparing Colombo IOL and IOLMaster 700, the 95% LoA of AL, CCT, AQD, ACD, LT, Kf, Ks, Km, AST, J0, J45, WTW and PD ranged from − 0.08 to 0.03 mm, − 21.58 to 5.09 μm, 0.01 to 0.15 mm, − 0.01 to 0.14 mm, − 0.05 to 0.10 mm, − 0.14 to 0.59 D, − 0.31 to 0.40 D, − 0.13 to 0.40 D, − 0.68 to 0.32 D, − 0.09 to 0.34 D, − 0.07 to 0.25 D, 0.11 to 1.47 mm, and − 0.97 to 2.31 mm, respectively. Conclusion The new SD-OCT-based Colombo IOL biometer demonstrates excellent repeatability and reproducibility. Moreover, it generally agrees well with the SS-OCT-based IOLMaster 700, except for the WTW and PD measurements.